Vascular function in women: when studying perimenopause is peri important - DuBose, Lyndsey E.; Lefferts, Wesley K. (Experimental physiology, 2023)
[...]we wish to highlight the importance of considering (i) the menopausal transition as a period of accelerated risk and clinical versus statistical significance, (ii) subject characteristics that may alter vascular ageing trajectories, and (iii) the paucity of data on cerebrovascular haemodynamics during menopause and importance of considering differing vascular methodology. [...]the limited literature examining cerebrovascular haemodynamics with menopause is inconsistent. [...]studies should comprehensively assess and report participant characteristics (i.e., physical activity, social determinants of health, menopause stage and symptoms) that may interact to alter vascular ageing trajectories across the menopausal transition and increase scientific reproducibility.